HUBUNGAN ANTARA SOKONGAN SOSIAL DENGAN STRES DALAM KALANGAN ANAK YATIM - Syawaluddin, Balqis; Aziz, Syazwana (Jurnal ’Ulwan, 2023)
Mental health issues among teenagers must be taken seriously by all parties because through good social support can help teenagers avoid mental health problems. The World Health Organization (WHO) states that 20 percent of children worldwide suffer from mental health problems, many of which go undiagnosed and untreated. This study was conducted to examine the relationship between social support and stress among orphans at the Fatimah Al-Zaharah Orphanage Complex, Bukit Katil, Melaka. The set of questionnaires consisting of three parts includes the respondent’s demographic information, the Inventory of Socially Supportive Behaviors (ISSB) questionnaire to measure social support and the Perceived Stress Scale-10 (PSS-10) questionnaire to measure stress. A simple random sampling method was chosen in conducting this study. All the data obtained was analyzed using the Statistical Package for the Social Sciences (SPSS) software version 25. The sample size taken for the survey design is 68 respondents. The results of the study found that there is no relationship between social support and stress among orphans at the Fatimah Al-Zaharah Orphanage Complex. Therefore, future studies can make improvements such as increasing the number of samples and expanding the study population so that it can be generalized to all orphans in orphanages. Next, add qualitative methods such as adding observation instruments and interviews on orphans to get more detailed information from respondents. In conclusion, with the production of this study, it can help the management especially at the Fatimah Al-Zaharah Orphanage Complex in identifying the level of stress of orphans as well as social support in the daily life of respondents.